Comparing the safety and efficacy of systemic therapies for high-risk biochemically recurrent hormone-sensitive prostate cancer: a network meta-analysis - Aprikian, Armen; Chilelli, Andrew; McLean, Thomas; Nasr, Anchen; Ganguli, Arijit; Serikoff, Alexis; Guzman, Franco; Barouma, Ifigeneia; Zacharioudaki, Maria; Freedland, Stephen J. (Frontiers in Oncology, 2025)
IntroductionEnzalutamide is the only androgen receptor pathway inhibitor approved by the United States Food and Drug Administration and the European Medicines Agency to treat high-risk biochemically recurrent non-metastatic hormone-sensitive prostate cancer. The objective of this network meta-analysis was to provide indirect evidence of the efficacy of enzalutamide relative to other therapies for biochemical recurrence after definitive therapy.Materials and MethodsWe conducted a systematic literature review to identify trials that assessed the efficacy and safety of current and emerging interventions. Outcomes of interest were metastasis-free survival, overall survival, time to prostate-specific antigen progression, time to castration resistance, proportion of patients with prostate-specific antigen <0.2 ng/ml at 36 (± 4) weeks of treatment, and grade ≥3 treatment-related adverse events. Fixed- and random-effects models were run under the Bayesian framework.ResultsEnzalutamide with androgen-deprivation therapy (i.e., combination therapy) demonstrated superiority over most comparators for overall survival (except androgen-deprivation therapy + docetaxel, which was similar), and over all comparators for metastasis-free survival, time to prostate-specific antigen progression, and time to castration resistance. Enzalutamide combination therapy demonstrated superiority over enzalutamide monotherapy for all efficacy outcomes, and similar performance for safety. Enzalutamide monotherapy demonstrated superiority over androgen-deprivation therapy alone and androgen-deprivation therapy + docetaxel for metastasis-free survival and time to prostate-specific antigen progression. Treatment-related adverse events were least common for androgen-deprivation therapy alone.DiscussionThis network meta-analysis provides evidence that enzalutamide combination therapy provides considerable oncological benefit in high-risk biochemically recurrent non-metastatic hormone-sensitive prostate cancer, albeit with a higher risk of treatment-related adverse events.